Islam Dan Nilai Toleransi Dalam Mencari Keadilan Sosial : Telaah Atas Konsistensi Perjuangan Masyarakat Di Daerah Moro-Moro - Ricco Andreas; Nandha Risky Putra (Nizham Jurnal Studi Keislaman, 2018)
Islam in terms of greeting (safety and pleasure) have values ​​of brotherhood, mutual respect and promote solidarity of the people in order to create a harmony in diversity. Form of mutual respect of diversity will always hand in hand with justice. Justice that the ideals for all human beings will always need a struggle. The struggle embodied in the values ​​of Islam is the provision of equality with others in order to create justice. So the struggle of Muslims must based on Oppressed people. Oppressed people who should be fought because of the loss of the rights and pleasures. If there are still oppressed people, the equality and justice has not come true. Islam is capable of churning into diversity must continue to fight for the oppressed until the creation of freedom to all mankind is fullfiled. Islamic values of struggle ​​we can found in the village of Moro-moro, Mesuji district. The state of society with diversity is no longer a problem. Because no longer any separation between individual interests and social interests. All united for the purpose of welfare with a tangible manifestation continue their mutual mutual assistance in economic sector in agriculture. Until into the making of houses of worship as the center of the struggle that is very individualistic society to do together in order to create prosperity